Health-related quality of life of children with Williams syndrome and caregivers in China - Chen, Weijun; Sun, Lidan; He, Xinyu; Li, Ziqiao; Ji, Chai; Li, Fangfang; Shen, Jiyang; Pan, Tianxin; Jin, Xuejing; Dong, Yusang; Hu, Lidan; Zou, Chaochun; et al. (Frontiers in Public Health, 2023)
Introduction: Williams Syndrome (WS) is a rare genetic disorder that impacts multiple systems and may cause developmental delays. These medical and developmental issues impose a heavy burden on affected children and their families. However, there was no study on children's health-related quality of life (HRQoL) with WS and only two studies about family quality of life globally. Therefore, the primary purpose of this study was to assess the HRQoL of children with WS and their caregivers in China, and the secondary purpose was to identify the potential determinants of children’s and caregivers’ HRQoL. Methods: In total, 101 children and caregivers were included. We applied the proxy-reported PedsQL 4.0 Generic Core Module (PedsQL GCM) and PedsQL 3.0 Family Impact Module (FIM) to measure the HRQoL of children and caregivers. Additionally, we collected information on a comprehensive set of social demographic and clinical characteristics. Differences in HRQoL scores across subgroups were assessed by two-independent-samples t-tests, one-way ANOVA, and posthoc tests. We also calculated effect sizes to indicate clinical relevance. Multivariate linear regression models were applied to assess the potential determinants of HRQoL. Results: We found that the HRQoL of children with WS and their caregivers was dramatically worse than the norm average scores of the healthy controls of children published in previous studies. Paternal educational level, household income, and the perceived financial burden significantly influenced the HRQoL of both children and families (p values < 0.05). Conclusion: We call for attention from policymakers and other stakeholders on the health status and well-being of children with WS and their families. Supports are needed to relieve psychosocial distress and financial burden.